A Palelintangan: Sasak Traditional Astronomy: Palelintangan: Astronomi Tradisional Sasak - Syaza, Nur Aini; Izzudin, Ahmad (Universitas Islam Negeri Mataram, 2023)
The people of Lombok and Bali initially used palelintangan, but in its development, the Balinese leaned more towards astrology. Most of the Sasak tribe, the people of Lombok, work as farmers and have been friends with nature since their ancestors existed. The evidence is that they utilize nature as a sign before carrying out their activities by calculating a lucky day or the right time, the beginning of the year, and changing seasons based on constellations, besides that natural signs are also considered. However, there has yet to be a complete study. What is palelintangan? How is the concept and implementation of palelintangan? Moreover, how does palelintangan affect the Sasak tribe? This study employs the library method. The main data source comes from a book entitled 'Traditional Astronomical Studies (Palelintangan) in Lombok, West Nusa Tenggara' and the additional data sources are taken from journals and scientific papers related to palelintangan. The data analysis's results discover that pelentangan is a traditional astronomy that has been implemented and was outlined in the form of wariga boards and rowot calendars to calculate the lucky days and determine the time related to the Sasak people's lives.